L'Art du ballet de cour en France, 1581-1643 - McGowan, Margaret M. 1931-2022 (Paris CNRS, 1963)
Margaret M. McGowan (born 1931) is a noted dance historian and historian of early modern France. Her work is primarily focused on the late Renaissance and the n-de-siècle period at the end of the nineteenth century. She did her dissertation at the Warburg Institute of the University of London under the supervision of Frances Yates, published subsequently as L'art du Ballet de Cour en France, 15811643. In addition to nearly a dozen books she has published over eighty articles and book chapters. McGowan is one of the first scholars to focus on the history of dance in the early modern period and served as Assistant Editor for the journal Dance Research for several decades, helping to shape the field of early dance.
Keywords: 16th Century (1501-1600); 17th Century (1601-1700); Ballet; Court; Iconography; History of dance; France